(untitled) (Advances in Applied Mathematics and Mechanics, 2023)
This investigation focused on the influence of the radial inertia effect on the propagation behavior of stress waves in thin-walled tubes subjected to combined longitudinal and torsional impact loads. Generalized characteristics theory was used to analyze the main features of the characteristic wave speeds and simple wave solutions in thin-walled tubes. The incremental elastic-plastic constitutive relations described by the rate-independent plasticity were adopted, and the finite difference method was used to investigate the evolution and propagation behaviors of combined elastic-plastic stress waves in thin-walled tubes when the radial inertial effect was considered. The numerical results were compared with those obtained when the radial inertia effect was not considered. The results showed that the speed of the coupled stress wave increased when the radial inertia effect was considered. The hardening modulus of the material in the plastic stage had a greater impact on the coupled slow waves than on the coupled fast waves.